KEBERHASILAN BAWASLU PROVINSI JAWA BARAT DALAM PENYELESAIAN SENGKETA PROSES PEMILU 2024 - Rahman, Isya Salsabila; Huda , Uu Nurul (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The purpose of this study is to examine and examine in depths related to the supervision of Bawaslu West Java Province in resolving disputes over the 2024 election process. Analyzing how the West Java Provincial Bawaslu exercises its authority as an election supervisor. This research uses empirical normative juridical methods because the problem to be studied relates to the authority of the West Java Provincial Bawaslu and observations made in the field. The results of the study state that the West Java Provincial Bawaslu has successfully resolved 16 disputes between election participants. All were resolved in mediation that had reached an agreement. Only 1 dispute was not resolved on the grounds that the status of the petition could not be accepted because it had passed the deadline. This proves that the West Java Provincial Bawaslu has been quite effective in carrying out its duties and authorities related to the handling of process dispute resolution in the 2024 elections.